Low methane emissions from Australian estuaries influenced by geomorphology and disturbance - Jacob Z.-Q. Yeo; Judith A. Rosentreter; Joanne M. Oakes; Bradley D. Eyre (Communications Earth & Environment, 2024)
Abstract Estuaries are a globally important source of methane, but little is known about Australia’s contributions to global estuarine methane emissions. Here we present a first-order Australia-wide assessment of estuarine methane emissions, using methane concentrations from 47 estuaries scaled to 971 Australian estuaries based on geomorphic estuary types and disturbance classes. We estimate total mean (±standard error) estuary annual methane emissions for Australia of 30.56 ± 12.43 Gg CH4 yr−1. Estuarine geomorphology and disturbance interacted to control annual methane emissions through differences in water–air methane flux rates and surface area. Most of Australia’s estuarine surface area (89.8%) has water–air methane fluxes lower than global means, contributing 80.3% of Australia’s total mean annual estuarine methane emissions. Australia is a good analogue for the ~34% of global coastal regions classified as less than moderately disturbed (>40% intact), suggesting that these regions may also have lower methane fluxes. On this basis, recent global estuarine methane emission estimates that do not consider disturbance in their upscaling, probably overestimate global estuarine methane emissions.